Analisis Pengaruh SWOT Pada PT. Coca-Cola Europacific Partners - Fatyandri, Adi Neka; Anggraini, Rina; Zaky, Muhammad Farhan (KOLEGIAL, 2023)
The purpose of this study was to determine and analyze the effect of the SWOT analysis on PT. Coca Cola Europacific Partners. Considering that SWOT is a method for making decisions in the best way, and is also capable of being developed and implemented in a company. In this study the SWOT matrix is also used to provide an overview and analysis of both internal and external opportunities and threats that will be faced so that the company is more alert in dealing with these matters. The method used is to analyze how a company develops its SWOT strategy in a more structured and better way. SWOT is a tool for managers in developing four very important types of strategies, namely Strengths, Weaknesses Opportunities, Strengths Threats and Weak Threats. Through this SWOT, managers can also produce effective and efficient marketing strategies to advance the business in a sustainable manner. The hope of the article that we created is to find out about compiling a SWOT strategy in a very structured and good way by collecting data that has been analyzed.